2018
DOI: 10.1177/0886260518794509
|View full text |Cite
|
Sign up to set email alerts
|

Child Appraisals of Interparental Conflict: The Effects of Intimate Partner Violence and Parent–Child Relationship Quality

Abstract: Children's appraisals of interparental violence, including appraisals of high threat and low coping efficacy, are robust predictors of behavioral and emotional problems. However, few studies have examined the factors that account for children's use of these maladaptive appraisals, particularly among children exposed to more severe forms of interparental conflict. The current study examines parent-child relationship quality as a mediator of the effect of intimate partner violence (IPV) exposure on children's ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 72 publications
1
16
1
4
Order By: Relevance
“…We also confirmed findings of various studies conducted in different cultures indicating that IPC may be related to poor parent-child relationship (e.g., Brock & Kochanska, 2016; Li et al, 2011), and that parent-child relationship may mediate the link between IPC and children’s IPC appraisals (e.g., Figge et al, 2018). However, previous studies evaluated either overall or a specific aspect (positivity and negativity) of the quality of the parent-child relationship as an intervening mechanism linking exposure to IPC with children’s IPC appraisals (see Figge et al, 2018; Fosco & Grych, 2007). In that sense, the present study extends prior findings by demonstrating the intervening role of different aspects of parent-child relationship (i.e., psychological control and attachment security) that is robust across child and parent gender.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We also confirmed findings of various studies conducted in different cultures indicating that IPC may be related to poor parent-child relationship (e.g., Brock & Kochanska, 2016; Li et al, 2011), and that parent-child relationship may mediate the link between IPC and children’s IPC appraisals (e.g., Figge et al, 2018). However, previous studies evaluated either overall or a specific aspect (positivity and negativity) of the quality of the parent-child relationship as an intervening mechanism linking exposure to IPC with children’s IPC appraisals (see Figge et al, 2018; Fosco & Grych, 2007). In that sense, the present study extends prior findings by demonstrating the intervening role of different aspects of parent-child relationship (i.e., psychological control and attachment security) that is robust across child and parent gender.…”
Section: Discussionsupporting
confidence: 89%
“…Past studies have shown that, besides its moderating function (e.g., DeBoard-Lucas et al, 2010; Grych, 1998; Grych & Fincham, 1990), the parent-child relationship plays a mediating role in the link between IPC and children’s appraisals of disputes (e.g., Figge et al, 2018). For instance, a cross-sectional study revealed that child-reported IPC is associated with parental positivity and negativity (i.e., parent-reported expressed positive and negative affect), which in turn is related to children’s self-blame appraisals (Fosco & Grych, 2007).…”
Section: Parent-child Relationship and Children’s Conflict Appraisalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that parenting higher conflict predicts increased internalized and externalized problems in children over four [28]. Interparental conflict was also associated with low coping efficacy mediated by mother-child relationships [29], inconsistent parenting, and low life satisfaction [15]. Therefore, interparental conflict may be understood in an integrated model whereas family processes, parenting, and individual, parents', and children's factors underlie the pathways to child adjustment, regulatory processes, psychological problems, and mental health in separation or divorce and post-divorce phases [30] and in different household arrangements [31].…”
Section: Parenting and Coparenting After Divorce Or Separationmentioning
confidence: 75%
“…Self-management strategies for distress in this sample likely reflect some of the therapeutic techniques learned in their mental and medical health groups (i.e., TPO group therapy, HIV/AIDS support group), but also reflect religio-cultural coping strategies, such as meditation, Buddhist teachings, blessings by monks, and ceremonies at the pagoda, which increase their sense of self-efficacy in coping with family violence. Coping efficacy, in the context of IPV, is a key factor in predicting children’s internalizing and externalizing outcomes (e.g., Figge et al, 2018). Family management of distress included advising and comforting parents in the context of IPV.…”
Section: Discussionmentioning
confidence: 99%